Pelaksanaan Manajemen Berbasis Sekolah (MBS) Pendidikan Kesetaraan Paket B di Sanggar Kegiatan Belajar (SKB) Diknas Kota Malang - Siswanto, Heru (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mojokerto, 2024)
ABSTRACT This research aims to 1. Find out how School Based Management (MBS) is implemented in the Malang City National Education Learning Activity Studio (SKB). 2. Know what factors hinder its implementation. And 3. Know what efforts have been carried out to overcome these inhibiting factors. This research is included in qualitative research, therefore the approach used is a qualitative descriptive approach. Meanwhile, the type of research is a case study. The results of this research show that the implementation of MBS in the Learning Activities Studio (SKB) of the Malang City National Education Office takes into account the seven basic school components that must be managed well. In relation to efforts to overcome the factors that hinder its implementation by implementing the Independent Curriculum development program on an ongoing basis, the development of teaching and education staff is carried out by encouraging teachers/tutors and business staff to develop their academic abilities, in the program for the development and fulfillment of facilities and infrastructure is carried out by utilizing funds APBD, APBN, DIPA, explore sources of funds originating from community participation through Committees, besides that programs are also determined based on a priority scale. Keywords: School Based Management